El tratamiento sobre estereotipos de género en los dictámenes del Comité de Eliminación de la Discriminación contra la Mujer (Tema Central) - Salgado Álvarez, María Judith (2018)
This article analyses the adoption of views of individual communications submitted to the Committee on the Elimination of Discrimination Against Women, in which the complainers allege and/or it is declared the violation of art. 5 a) of the Convention on the Elimination of All Forms of Discrimination Against Women, which determines the obligation of State Parties to modify the social and cultural patterns of conduct of men and women, with a view to achieving the elimination of prejudices and customary and all other practices which are based on the idea of the inferiority or the superiority of either of the sexes or on stereotyped roles for men and women. It points out the limits and contributions that we find out in the Committees treatment on gender stereotypes and its incidence on violence and discrimination against women. It defends the need to pay accurate attention to the identification of gender stereotypes linked with women´s subordination, to overcoming them. For this purpose, the CEDAW interpretative developments, expressed, among others, in its adoption of views constitute an unavoidable source both for the approval of legislation and public policies as for justice administration.